Epithelioid glioblastoma exhibits a heterogeneous molecular feature: A targeted next-generation sequencing study - Pan, Rui; Wang, Xiaotong; Fang, Ru; Xia, Qiuyuan; Wu, Nan; Rao, Qiu (Frontiers in Oncology, 2022)
Introduction Epithelioid glioblastoma (eGBM) is one of the rare glioblastoma (GBM) variants in the current World Health Organization (WHO) categorization of central nervous system (CNS) tumours. However, the diagnostic basis and molecular features of eGBM have not been clearly defined to date. In this study, we aimed to molecularly characterize these tumours. Methods The clinicopathological, molecular, and immunohistochemical characteristics of 12 cases of eGBM were investigated. Results The tumours were found to be made up of epithelioid and rhabdoid cells when examined under a microscope. Six cases (50%) harboured the BRAF V600E mutation, and NF1 mutation was detected in 2 eGBM cases (16.7%). CDKN2A/B homozygous deletion was seen in 5 cases (41.7%). TP53 mutation was recognized in 2 instances (16.7%), and TERT promoter mutation was recognized in 5 cases (41.7%). Discussion eGBM is characterized by high molecular heterogeneity and has molecular overlaps between low-grade gliomas. Moreover, rather than being a variant or entity, the biological significance of the "epithelioid" appearance may be reduced to a simply morphological pattern. In order to target the proper treatment to suitable patients, molecular stratification via genome-wide molecular profiling will be crucial.